(untitled) (Singapore, 1997)
The quantum Monte Carlo (QMC) method is gaining interest as a complement to basis set ab initio methods in cases where high accuracy computation of atomic and molecular properties is desired. This volume focuses on recent advances in this area. QMC as used here refers to methods that directly solve the Schrödinger equation, for example, diffusion and Green's function Monte Carlo, as well as variational Monte Carlo. The latter is an approach to computing atomic and molecular properties by the Monte Carlo method that has fundamental similarities to basis set methods with the exception that the limitation to one-particle basis functions to facilitate integral evaluation is avoided.
Keywords: Quantum field theory,Lý thuyết trường lượng tử